2006
DOI: 10.1590/s0037-86822006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Successful therapeutic response of resistant cases of mucocutaneous leishmaniasis to a very low dose of antimony

Abstract: Two mucocutaneous leishmaniasis cases resistant to therapy are reported here. After the failure of initial therapies (antimony, amphotericin B and/or pentamidine) patients received a low-dose schedule: one ampoule of meglumine antimoniate (405mg of pentavalent antimony [Sb v ]) by intramuscular injection, three times a week until complete healing of the lesions. One patient was cured with a total of 30 ampoules in 10 weeks and the other received 36 ampoules in 12 weeks. Both remain clinically cured after one y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Since the mid-1980s, low dose regimen has been employed at our institution in Rio de Janeiro, Brazil, to treat patients with cutaneous and mucosal leishmaniasis [15–21, 24, 30, 34]. The rationale behind it is intuitively attractive and relies on its expected non-inferior effectiveness, less toxicity, improved compliance and reduced costs [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the mid-1980s, low dose regimen has been employed at our institution in Rio de Janeiro, Brazil, to treat patients with cutaneous and mucosal leishmaniasis [15–21, 24, 30, 34]. The rationale behind it is intuitively attractive and relies on its expected non-inferior effectiveness, less toxicity, improved compliance and reduced costs [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested that low dose regimen is apparently effective, evidence was scarce and based mainly on case reports and observational studies [16, 1824]. High dose of antimony is the current standard of care for most patients with ACL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different doses have been evaluated, and doses other than the recommended dose are occasionally used; however, the decision to use a different dose must be based on structured studies within the same area and with the same Leishmania species. 48,49 The cure rate after treatment using pentavalent antimonials varies from 30% to 90%. 50 Because some reports using liposomal amphotericin B formulations for the treatment of ML have shown excellent results, liposomal amphotericin B can be an alternative treatment; however, the optimal doses for the treatment of ML have not been completely defined.…”
Section: MLmentioning
confidence: 99%